Perbedaan Terapi Akupresure Titik Sp4 dan Aromaterapi Peppermint Pada Ibu Hamil Dengan Emesis Gravidarum - Windi Kusuma, Fadila; Rini, Ageng Septa; Fatimah, Jesy (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Emesis gravidarum is one of the most common conditions experienced by pregnant women, especially during the first trimester. These symptoms include nausea and vomiting, which often disrupt daily routines and reduce the quality of life of pregnant women. Globally, the prevalence of emesis gravidarum is estimated to occur in 50-90% of pregnant women with varying degrees of severity. This study aims to understand the difference in effectiveness between acupressure therapy at the Sp4 point and peppermint aromatherapy in first-trimester pregnant women with emesis gravidarum at TPMB Bidan Desti Arisanti Bogor in 2025. The method used is a Quasi Experiment with a two-group pre- and posttest approach. The sample in this study were 30 pregnant women in the second trimester with anemia. The measurement tool used was an observation sheet. The results of this study obtained 17 pregnant women (56.7%) with mild nausea and vomiting, before being given peppermint aromatherapy intervention, 9 pregnant women (26.7%) experienced mild nausea and vomiting and after the intervention did not experience nausea and vomiting 11 pregnant women (73.3%), before being given Sp4 acupressure therapy intervention, 8 pregnant women (53.3%) experienced mild nausea and vomiting and after the intervention did not experience nausea and vomiting as many as 7 pregnant women (46.7%), it was found that peppermint aromatherapy and acupressure therapy at the Sp4 point both effectively reduced the level of emesis gravidarum in pregnant women in the first trimester at TPMB Midwife Desti Arisanti Bogor in 2025 with a p value of 0.001 <0.05 and a mean difference of 0.53. There is a difference in the effectiveness of SP4 acupressure therapy and peppermint aromatherapy on emesis gravidarum in first-trimester pregnant women. Keywords: SP4 Acupressure Therapy, Peppermint Aromatherapy, Pregnant Women, Emesis Gravidarum